The manipulative facet of translating implicit communication: challenges and implications from both theoretical and empirical perspectives - Viviana Masia (Linguistik Online)
This paper examines the implications of translation choices that fail to consistently render implicit strategies from a source language into a target language. In the heterogeneous framework of implicit communication phenomena, this paper investigates the translation of presuppositions, implicatures, and topic-focus structures. Furthermore, it highlights how their consistent or inconsistent rendering into other languages might make a translated text manipulative. These instances are substantiated by examples from different text genres, including novels and official translations of political speeches in the English-Italian, English-Spanish, and Spanish-Italian language directions. Besides suggesting strategies for implicit communication that prevent translated texts from becoming dangerously manipulative, this paper seeks to raise awareness about (i) the ways linguistic manipulation can affect the target readership and (ii) the risks posed by manipulating translations to socially constructed knowledge as well as the creation of a democratically grounded consensus.